Management and Outcomes of Diffuse Axonal Injury in patients with Road Traffic Accidents - ZAHID, HASSAAN; HASNAIN, HAFIZ MUHAMMAD ALI; NAJEEB, ZIA UL REHMAN NAJEEB; SOHAIL, ASIF SOHAIL (Pakistan Journal of Medical & Health Sciences, 2025)
Objectives: The authors were trying to examine management and outcome of diffuse axonal injury (DAI) among road traffic accident (RTA) victims. In particular, we targeted the clinical results, mortality, and recovery procedures of a group of 130 patients. Methods: A retrospective study will be carried out using a sample comprising of 130 patients diagnosed with diffuse axonal injury as a result of road traffic accident. The information has been gathered on the demographic factors, injury severity, management procedures and clinical outcomes. Initial assessment was performed by the use of the Glasgow Coma Scale (GCS), and Magnetic Resonance Imaging (MRI) was done to validate the diagnosis. The outcomes were categorized under recovery, partial recovery, or death. Results: The researchers discovered that the baseline GCS score and the period between injury and treatment were significantly correlated with the severity of DAI. About 60 percent of patients were in need of intensive care and 40 percent partially or never recovered even after 6 months. Conclusion: Management that is initiated early in life particularly in the first 24 hours was established to have significant effects on the recovery of the patients. Further research is needed to refine the treatment protocols and improve outcomes in DAI cases.